Enhanced Bluetooth Low Energy 5 Aodv-Based Mesh Communication Protocol With Multipath Support - Ghori, Muhammad Rizwan (2023)
Wireless Ad-Hoc Networks (WAHN) are growing more widespread due to improvements in Internet of Things (IoT) technologies. Several WAHN technologies, including ZigBee, Z-Wave, Threads, Bluetooth Low Energy (BLE) are available. Despite progress on IoT, network-based routing continues to be a critical problem that has to be tackled. In view of the above, this study focuses on a BLE-based mesh network.